Auditoria en seguridad vial en el tramo: Obando-Zaragoza (2022)
n this work, the Road Safety Audit was developed for the Obando-Zaragoza section from Km 57 + 000 to Km 66 + 000 to the signaling, vehicular containment barriers and geometric design that make up the road, to determine its condition in front of the actors roads that circulate through it. For this, the quantitative methodology was used, the operationalization of the objectives was carried out and through data collection instruments such as checklists and speed and photographic records, the field work was carried out, the most important findings show that there is no correlation between the Indices of road accidents and compliance with the standard of the audited variables, it was evidenced that although these present failures and inconsistencies, they do not affect the accident rate, what could be evidenced is that the behavior and improper actions of the users are the cause of her, thus speeding and not keeping a safe distance, occupy the first place and in second place is overtaking closing.